Chemical looping deoxygenated gasification: An implication for efficient biomass utilization with high-quality syngas modulation and CO2 reduction. (1st July 2020) - Sun, Zhao; Chen, Zong; Toan, Sam; Sun, Zhiqiang
Graphical abstract: Highlights: A novel pathway, chemical looping deoxygenated gasification (CLDG), was proposed; The CLDG synergistically achieves biomass-derived syngas refinement and CO2 reduction; The H2 /CO molar ratios from 0.49 to 2.57 can be obtained by modulating H2 O and CO2 ; The biomass gasification efficiency increases by 35.9% under the optimized conditions. Abstract: Chemical looping gasification is a promising technology for biomass utilization. However, the biomass-derived products contain tar and CO2, which seriously affects the syngas quality and hinders its development. A new approach, chemical looping deoxygenated gasification (CLDG), was proposed for high-quality, H2 /CO-tunable syngas generation with CO2 utilization via redox looping of CaO + Fe ↔ Ca2 Fe2 O5 . The CLDG process involves a deoxygenation reactor (DR) and a regeneration reactor (RR). Fe 0 continuously reduces the oxygen-containing species to drive high-quality syngas production in the DR, and the oxidized oxygen carrier (Fe 3+ ) can be reduced under CO in the RR. A thermodynamic simulation was conducted to verify the feasibility of CLDG using Aspen Plus. The effects of DR and RR temperatures, of the molar ratios of Fe/Obio, CO2 /C, H2 O/C, and (C + CO)/Fe on the syngas quality, H2 /CO molar ratio, and the efficiency of gasification, chemical looping deoxygenation, and CO2 reduction were investigated intensively and optimized to guide the CLDG process. The results indicate that CLDG can significantly improve the quality of syngas with various H2 -to-CO syngas modulations and CO2 reduction, obtaining a lower heating value (LHV) of 9.07 MJ/m 3, a gasification efficiency of 96.31%, a CO2 reduction efficiency of 44.51%, an H utilization efficiency of 79.52%, and a chemical looping deoxygenation efficiency of 17.55%.